Seismic performance of precast RC column to steel beam connections with variable joint configurations. (1st April 2018) - Khaloo, Alireza; Bakhtiari Doost, Rooholah
Highlights: Shifting the connection failure from beam to joint to evaluate the joint performance. Simulation of seismic load by testing precast connections under reversal displacement. Evaluating the influence of shear keys and extended cover plates on the joint response. Abstract: In the last decades, noticeable experimental and analytical investigations have been carried out on cast-in-place Reinforced Concrete column to Steel beam (RCS) connections, however rarely have been conducted on the precast RCS. In this paper, test results of four half-scale interior precast RCS connections with variable joint configurations are presented. The steel beams were connected to the precast column, using three specimens with extended face bearing plates and one with extended cover plates, embedded in the connection zone. The flanges of beams were strengthened with respect to scaled section, in order to increase the load transfer to the joint. All samples were loaded under reversed displacement controlled condition. The failure mode, joint distortion, lateral load capacity, stiffness retention, stiffness degradation and energy dissipation capacity were evaluated. Presence of shear keys in the joint enhances strength and stiffness of subassemblies and reduces joint distortion. Utilization of extended cover plates considerably reduces shear distortion and rigid body rotation and also significantly increases shear resistance of the joint.